P295 Evaluation Of French Microbiology Laboratories Practices Concerning Antibiotic Therapy And Antimicrobial Resistance. (15th August 2013) - Durocher, A; Vernet-Garnier, V; Cornille, M; Delzenne, M; Methenni, M; Rousseau, D; Van Hecke, E
Abstract : Background: Guidelines on prevention of bacterial resistance and quality of microbiology labs have been promoted by HAS. Objectives: Analysis of implementation of guidelines in 2011 versus 2009. Methods: Checklists for practices of 230 representative hospital labs. Results: Between 2009 and 2011, there was an increase in (i) survey of bacterial resistance by labs (98% vs 95%), (ii) internal quality control (88% vs 85% of public, 71% vs 64% of private labs -p = 0.01), (iii) evaluation of procedures (67% vs 57% -p = 0.01), (iv) basic service maintained in 89% vs 85% of labs, (v) information system (96% vs 88% of public, 82% vs 75% of private labs -p = 0.003), (vi) liaison with the pharmacy (86% vs 78% of public, 76% vs 63% of private labs), (vii) epidemiological surveillance (96% vs 87%), (viii) alert system (97% vs 93%) mostly by computer in public or by phone in private labs). Results on resistance rates were more often submitted to the committee for the prevention of hospital infection (97% vs 93%) or of anti-infectives (77% vs 71%), to the clinical departments in 62% vs 50% of public, 85% vs 75% of private hospitals (p = 0.018). Bacterial resistances were more often compared with antibiotic consumption in 57% vs 45% of general, 86% vs 61% of university, 37% vs 34% of private hospitals (p = 0.002) Conclusions: Quality of microbiology laboratory practices increased since 2009 but efforts have to be continued in evaluation of internal quality procedures, communication about bacterial resistances to clinical departments and comparison resistances-antibiotic consumption.